Study skills for academic writing - Trzeciak, John (Longman, 1994)
The book has five units. The aims of each unit are set out briefly on the first page of the unit. The first section gives information and advice that you will require in the tasks that form the second section of the unit. Some short tasks are occasionally included in the guide section.